1996
DOI: 10.1021/js960106l
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Iontophoretic Transport Paths in Cultured and Animal Skin Models

Abstract: Physiological structures associated with iontophoretic paths in hairless mouse skin and two cultured skin models ("EpiDerm" by Mattek, Corp., and "SKIN2" by Advanced Tissue Sciences, Inc.) are reported. Visualization of ionic paths at current densities between 20 and 100 microA/ cm2 is accomplished by the counterdirectional transport of Fe(CN)6(4-) and Fe3+, resulting in the controlled precipitation of colloidal Prussian blue, Fe4[Fe(CN)6]3, at sites of high ionic conductivity. Examination of the Fe4[Fe(CN)6]3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…Visualization studies have suggested the primary route through the stratum corneum is the located in or near the skin appendages 19. Other biophysical investigations indicate that ion and water transport occurs, at least in part, through the polar region of the intercellular lipid lamellae 20,21. Therefore, enhancers that exert an effect in these regions are more likely to synergistically enhance iontophoretic permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Visualization studies have suggested the primary route through the stratum corneum is the located in or near the skin appendages 19. Other biophysical investigations indicate that ion and water transport occurs, at least in part, through the polar region of the intercellular lipid lamellae 20,21. Therefore, enhancers that exert an effect in these regions are more likely to synergistically enhance iontophoretic permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The changes by iontophoresis, including decreases in skin impedance [27,28], deprivation of epidermal calcium [25], and the suggestion that the proposed pathways of iontophoresis are pores [29][30][31], hair follicles [32] and sweat ducts imply that spaces with decreased electric impedance may be easy iontophoretic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of iontophoretic transport, the transappendageal route via the hair follicles and sweat ducts predominates [39]. Lai and Roberts [38] showed that most small solutes are transported through a pore with radii of 6.8-17 Å, which is consistent with transport through the polar intercellular and transappendageal pathway.…”
Section: Pioneering New Technologiesmentioning
confidence: 91%